(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The use of innovative approaches in military affairs allows achieving significant success both on the battlefield and in training. The world's leading armies are considering modernizing the physical training of female military personnel and have focused on finding ways to improve the physical fitness of female servicewomen. Unfortunately, the overemphasis in military history and legacy on aerobic fitness and “field expediency” as the primary criteria for training implementation has limited the extent to which the military has fully implemented state-of-the-art PT policies. This inherited approach can be problematic in fully enhancing women's ability to perform physically demanding combat tasks and can put the successful integration of women into ground combat MOSs at significant risk. Purpose: to get acquainted with the introduction of new ideas and technologies in the physical education of female servicemen in both Ukrainian and foreign armies and, based on the results obtained, to propose directions for improving the level of physical fitness of female servicemen of the Armed Forces of Ukraine. Material and Methods: Analysis of scientific literature and documentary sources on the problems of physical training of female servicewomen; generalization and systematization of theoretical knowledge related to the trends in the development of physical training of female servicewomen in the scientific and methodological literature. Results: Some Ukrainian scholars have considered the use of innovative approaches to improve the physical fitness of military personnel. The study found that the armed forces of the United States of America and the United Kingdom have created special research units that have been conducting in-depth research on the problems of physical training of female servicewomen in the modern army over the past ten years. The use of the following technologies has been established: information and communication, differentiated physical education, and health preservation technology. In addition, the above countries are developing a physical training strategy to optimize the performance of women servicewomen in combat professions. Conclusions. Having analyzed the scientific works of Ukrainian and foreign authors, it should be noted that in order to improve the level of physical fitness of female servicewomen, it is necessary to use technologies that allow taking into account the physiological characteristics of women and using the strengths of the female body when creating physical training programs for female servicewomen in combat specialties.